Preferential association of a functional variant in complement receptor 2 with antibodies to double-stranded DNA (2016)
Objectives Systemic lupus erythematosus (SLE; OMIM 152700) is characterised by the production of antibodies to nuclear antigens. We previously identified variants in complement receptor 2 (CR2/CD21) that were associated with decreased risk of SLE. This study aimed to identify the causal variant for this association. Methods Genotyped and imputed genetic variants spanning CR2 were assessed for association with SLE in 15 750 case-control subjects from four ancestral groups. Allele-specific functional effects of associated variants were determined using quantitative real-time PCR, quantitative flow cytometry, electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP)-PCR. Results The strongest association signal was detected at rs1876453 in intron 1 of CR2 (pmeta=4.2×10-4, OR 0.85), specifically when subjects were stratified based on the presence of dsDNA autoantibodies (case-control pmeta=7.6×10-7, OR 0.71; case-only pmeta=1.9×10-4, OR 0.75). Although allele-specific effects on B cell CR2 mRNA or protein levels were not identified, levels of complement receptor 1 (CR1/CD35) mRNA and protein were significantly higher on B cells of subjects harbouring the minor allele (p=0.0248 and p=0.0006, respectively). The minor allele altered the formation of several DNA protein complexes by EMSA, including one containing CCCTC-binding factor (CTCF), an effect that was confirmed by ChIP-PCR. Conclusions These data suggest that rs1876453 in CR2 has long-range effects on gene regulation that decrease susceptibility to lupus. Since the minor allele at rs1876453 is preferentially associated with reduced risk of the highly specific dsDNA autoantibodies that are present in preclinical, active and severe lupus, understanding its mechanisms will have important therapeutic implications.